Exploiting microalgal diversity for sterol production - Omnia H. Abdelkarim; Omnia H. Abdelkarim; Rene H. Wijffels; Rene H. Wijffels; Maria J. Barbosa (Frontiers in Plant Science)
Sterols are essential for eukaryotic cell membrane integrity and fluidity, and they demonstrate valuable pharmaceutical and nutraceutical benefits, including anti-inflammatory, antioxidant, anti-cancer, and cholesterol-lowering properties. Traditionally, animal, plant, and microbial fermentation sterols face sustainability, economic, and ethical challenges. Microalgae have emerged as a promising alternative due to their biochemical diversity, rapid growth, and controlled cultivation capabilities. This review explores microalgae’s potential for sterol production, highlighting their advantages, including sustainability and sterol profile diversity, while addressing key challenges of low sterol yields, species-dependent variations, and industrial scalability. We discuss how recent advancements in metabolic engineering, cultivation technologies, and process optimization could enhance sterol production. By integrating innovative biotechnological strategies, microalgae hold the potential to become a viable and sustainable sterol source for pharmaceutical, nutraceutical, and industrial applications.